Primary tumor‐secreted VEGF induces vascular hyperpermeability in premetastatic lung via the occludin phosphorylation/ubiquitination pathway. Issue 12 (25th September 2019) - Li, Ranran; Qi, Yana; Jiang, Man; Zhang, Tiehong; Wang, Hongwei; Wang, Liguang; Han, Mingyong
Abstract: Primary tumor can induce the formation of premetastatic niche. The hyperpermeability of the vessels in the premetastatic niche is the first step in the development of metastasis. However, the cellular and molecular mechanisms of vascular hyperpermeability remain to be elucidated. In this study, 4T1 breast cells were injected into the breasts of mice to establish a tumor model. Our results showed that primary tumors induced hyperpermeability of the vessels in the premetastatic lung. Subsequent studies showed that the level of vascular endothelial growth factor (VEGF) was elevated in the tumor‐bearing mice serum and the levels of tight junction (TJ) proteins occludin and ZO‐1 were decreased in the premetastatic lung. In vitro studies demonstrated that VEGF increased the permeability of dextran and decreased the levels of occludin and ZO‐1 in human umbilical vein endothelial cells. Moreover, the hyperpermeability of vessels and the degradation of occludin was blocked by bevacizumab. Overexpression of occludin alleviated the VEGF‐induced hyperpermeability. Further investigations revealed that VEGF‐induced occludin phosphorylation at Ser‐490 and ubiquitination. Finally, we showed that VEGF accelerated the process of occludin degradation through the ubiquitin‐proteasome system. In conclusion, primary tumor‐secrete VEGF induce the occludin phosphorylation/ubiquitination and downregulation, resulting in the disruption of TJs and hyperpermeability of vessels in premetastatic lung. The occludin phosphorylation/ubiquitination pathway may be the mechanism of VEGF‐induced vascular hyperpermeability in the lung premetastatic niche.